Experiences of Adolescents and Emerging Adults Living With Type 1 Diabetes. Issue 2 (April 2019) - Datye, Karishma; Bonnet, Kemberlee; Schlundt, David; Jaser, Sarah
Purpose: The purpose of this study was to identify barriers to adherence in type 1 diabetes through adolescent focus groups and to use this information to determine how diabetes educators can have a positive impact on their patients' diabetes management. Methods: Two focus groups were conducted with adolescents and young adults (n = 11) ages 17 to 21 with type 1 diabetes. A focus group script, which consisted of 4 open-ended questions about diabetes care and challenges associated with management of diabetes, was used to elicit discussion. The focus group transcripts were coded and analyzed using the inductive-deductive approach. Results: Participants described unique barriers to and facilitators of self-care behaviors in their management of type 1 diabetes. A conceptual framework was developed to describe adherence to self-management in adolescents with type 1 diabetes. Biological, psychological, and environmental situational influences emerged that influence self-care behaviors. In addition, facilitators of self-care behaviors, including the health system and diabetes education, were identified, and together the interaction between situational influences, facilitators, and self-care behaviors influenced adherence to diabetes treatment. Conclusions: The conceptual framework based on these focus groups may help diabetes educators assess and address barriers to self-care behaviors in adolescents and young adults with type 1 diabetes.